2010
DOI: 10.4111/kju.2010.51.11.745
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Perineural Invasion and Its Prognostic Value in Patients with Prostate Cancer

Abstract: PurposeThe prognostic significance of perineural invasion by prostate cancer is debated. We investigated the association between perineural invasion and clinicopathological factors and the effect of perineural invasion on survival in patients with prostate cancer.Materials and MethodsA total of 361 patients with prostate cancer without any neoadjuvant therapies prior to surgery from 1999 to 2010 were analyzed retrospectively. Whole-mount sections of surgical specimens from all patients who underwent radical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 18 publications
1
27
2
Order By: Relevance
“…This is likely explained by the fact that we used a strict definition of PNI, that of circumferential encirclement of nerves by malignant glands. In contrast, prior studies reporting a higher PNI prevalence either did not describe how PNI was defined (14, 19, 20, 25, 39) or used vague descriptions such as presence of tumor cells “in the perineural space” (16, 18) or “along the perineural sheath” (21). Because the perineural space can often be difficult to identify using H&E stains alone, abutment of the perineural space by both malignant and benign glands can, in the absence of circumferential involvement, be misinterpreted as PNI (53, 54), resulting in misclassification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is likely explained by the fact that we used a strict definition of PNI, that of circumferential encirclement of nerves by malignant glands. In contrast, prior studies reporting a higher PNI prevalence either did not describe how PNI was defined (14, 19, 20, 25, 39) or used vague descriptions such as presence of tumor cells “in the perineural space” (16, 18) or “along the perineural sheath” (21). Because the perineural space can often be difficult to identify using H&E stains alone, abutment of the perineural space by both malignant and benign glands can, in the absence of circumferential involvement, be misinterpreted as PNI (53, 54), resulting in misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…Of the more than 30 studies that have examined the association between PNI in radical prostatectomy specimens and prostate cancer outcomes (see Table 2), only three (18, 26, 38) have assessed whether PNI predicts distant metastases or death, with the remainder focusing on biochemical recurrence as the outcome of interest. This is important given that most men who develop a biochemical recurrence are not destined to die of their disease (4446).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of studies have found that PNI predicts BCR on univariable analysis, [7][8][9][10][11][12][13][14][15] only two studies have reported PNI as a significant predictor on multivariable analysis. 8,13 Both of these studies examined relatively small cohorts of fewer than 250 participants.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] Jeon et al [49] also reported that patients with PNI have higher GS, ECI, SVI, and PSM. Lee et al's [50] 2010 study showed that PNI presence was related to lymph node invasion, higher GS, PSM, higher tumor volume, and late-term PC; however, PNI was not an independent risk factor for BCR in multivariate analysis. Our study results were similar to the ones in the literature that show no relation between PNI and BCR (p=0.548).…”
Section: Discussionmentioning
confidence: 98%